2011
DOI: 10.1002/stem.753
|View full text |Cite
|
Sign up to set email alerts
|

MEK-ERK Signaling Dictates DNA-Repair Gene MGMT Expression and Temozolomide Resistance of Stem-Like Glioblastoma Cells via the MDM2-p53 Axis

Abstract: Overcoming the resistance of glioblastoma cells against temozolomide, the first-line chemotherapeutic agent of choice for newly diagnosed glioblastoma, is a major therapeutic challenge in the management of this deadly brain tumor. The gene encoding O 6 -methylguanine DNA methyltransferase (MGMT), which removes the methyl group attached by temozolomide, is often silenced by promoter methylation in glioblastoma but is nevertheless expressed in a significant fraction of cases and is therefore regarded as one of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
82
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(87 citation statements)
references
References 36 publications
(46 reference statements)
0
82
0
5
Order By: Relevance
“…Another interesting finding of our study is that MEK2 inhibitors could be used as a sensitizing strategy for TMZ treatment. Here, the administration of trametinib (GSK1120212) and PD184352 (CI-1040), two MEK1/2 inhibitors undergoing clinical trials 41 , greatly altered the apoptotic rate of glioma cells upon TMZ treatment. Notably, these inhibitors are nonselective inhibitors to MEK1 and MEK2, and the contribution of MEK1 inhibition in improved TMZ sensitivity should be further investigated in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Another interesting finding of our study is that MEK2 inhibitors could be used as a sensitizing strategy for TMZ treatment. Here, the administration of trametinib (GSK1120212) and PD184352 (CI-1040), two MEK1/2 inhibitors undergoing clinical trials 41 , greatly altered the apoptotic rate of glioma cells upon TMZ treatment. Notably, these inhibitors are nonselective inhibitors to MEK1 and MEK2, and the contribution of MEK1 inhibition in improved TMZ sensitivity should be further investigated in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively the activation of ERK is involved with the maintenance of the expression of MGMT and resistance to TMZ of GBM-GICs. [32] As previously mentioned GAS1 inhibits the activation of ERK1/2, thus it may promote the elimination of the GIC´s population [ Figure 2]. It is relevant that the overexpression of GAS1 in human adenocarcinoma cells (A549) increases their sensibility to cisplatin, which inhibits proliferation and induces cell cycle arrest and apoptosis.…”
Section: Potential Therapeutic Effect Of Gas1 For the Treatment Of Glmentioning
confidence: 95%
“…[26,28,30] It is noteworthy that CD133 + GICs are predisposed to become resistant to chemo-and radiotherapy with respect to non-GICs cells, implicating the activation of extracellular signal-regulated kinases 1 and 2 (ERK1/2). [20,31,32] In this context, the use of classical therapies against gliomas, facilitate the selection of multi-resistant GICs, leading to the formation of more aggressive tumors, resistant to chemo-and radiotherapy. [33] Moreover, in vitro and in vivo studies have shown that with the adequate stimulus, GICs differentiate to either neuronal or astrocytic cells, however many of these responses are deregulated in gliomas.…”
Section: Molecular Approach Against Multi-resistant Gliomasmentioning
confidence: 99%
“…More recently, the use of a mitogen-activated protein/extracellular signal-regulated kinase (MEK) inhibitor has shown promise as a TMZ adjuvant by activating p53 [65]. Molecules targeting miRNAs may also be effective at p53-mediated suppression of MGMT.…”
Section: O6-benzylguaninementioning
confidence: 99%